Embedding Formative Assessment and Promoting Active Learning - Elizabeth Swinbank; Mary Whitehouse; Robin Millar (Karolinum Press, 2017)
In this contribution we outline how the York Science project is using a 'backward design' approach to teaching science to students aged 11-14. We then present some examples of formative assessment tasks and show how simple selected-response questions can be modified to provide teachers with detailed information about students' ideas. Finally we indicate how such tasks can help promote active learning.